Case Report: Acquired CDKN2A/B deletion and mTOR inhibitor resistance in TSC2-mutant metastatic epithelioid angiomyolipoma - Shuai He; Jing Yang; Jiguang Yang; Chunxia Li; Juan Shen; Xiaolong Ye; Zuping Liu; Wenhao Shen; Jun Zheng; Yongquan Wang (Frontiers in Medicine, 2026)
Acquired resistance to mTOR inhibition remains a major challenge in TSC2-mutant metastatic epithelioid angiomyolipoma (EAML). We report a 30-year-old woman with metastatic EAML harboring biallelic TSC2 mutations who achieved a complete response to everolimus but developed disease progression after 16 months. Tumor rebiopsy revealed persistent TSC2 mutations and acquired CDKN2A/B deletion, accompanied by increased Ki-67 and emergence of TFE-3 immunoreactivity and focal S-100 positivity. These findings suggest a potential association between CDKN2A/B loss and aggressive tumor behavior after mTOR inhibition, although causality remains unproven. CDK4/6-targeted strategies may warrant further investigation in this context.